SOCIAL REHABILITATION OF VICTIMS OF TRAFFICKING IN PERSONS IN INDONESIA: A QUALITATIVE STUDY OF PROBLEMS AND RESPONSE EFFORTS - Moch Zaenal Hakim; Meiti Subardhini; Silvia Fatmah Nurusshobah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Trafficking in persons, or human trafficking, is a complex form of human rights violation because it involves exploitation, violence, deception, abuse of a position of vulnerability, and weak social protection for victims. This study aims to analyze the profile of trafficking in persons in Indonesia, identify response efforts undertaken by government and non-governmental organizations, and formulate a social rehabilitation model for victims of trafficking in persons. The study employed a qualitative approach using a case study method. Data were collected through documentation studies, in-depth interviews, and focus group discussions with victims of trafficking in persons, victims' families, case workers, and administrators of the Indonesian Migrant Workers Union (Serikat Buruh Migran Indonesia/SBMI) at the research sites. The findings show that victims of trafficking generally come from poor families, have low levels of education, face limited access to decent work, and are recruited through non-procedural channels. Victims experienced labor exploitation, physical and psychological violence, document confiscation, communication restrictions, unpaid wages, and psychosocial trauma. Current case responses remain dominated by repatriation, legal advocacy, and family reunification, while post-trauma social rehabilitation has not yet been implemented systematically. From a social work perspective, victims of trafficking require a person-in-environment approach, trauma-informed care, a rights-based approach, case management, and socio-economic reintegration. This study recommends an integrated social rehabilitation model that includes identification, comprehensive assessment, initial protection, shelter services, psychosocial support, legal assistance, health services, economic empowerment, family reunification, social reintegration, and continuous monitoring.